1997
DOI: 10.1128/jcm.35.1.292-294.1997
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of eight enzyme immunoassays for detection of immunoglobulin G against Helicobacter pylori

Abstract: Eight commercial enzyme-linked immunosorbent assays (ELISAs) were used to test sera taken from 102 patients in whom Helicobacter pylori infection status had been determined by means of biopsy culture, PCR, histology, and urease production and by 13 C urea breath test. By those means, 61 patients had been found to be infected. Assays were compared by receiver operating characteristic analysis. Sensitivities ranged from 86 to 98%; specificities ranged from 83 to 98%. In a group consisting of the assays by Bio-Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…The parameters of these assays vary with sensitivity ranging between 81 and 100% and specificity between 79 and 98%. 3,9,10 Previous studies have shown that the performance of diagnostic kits is often poor in geographically different regions, possibly because of the use of less relevant antigens. 4,11 In the present study, the whole-cell antigen extract from the H. pylori strain NCTC 11637 gave reasonable accuracy in an Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of these assays vary with sensitivity ranging between 81 and 100% and specificity between 79 and 98%. 3,9,10 Previous studies have shown that the performance of diagnostic kits is often poor in geographically different regions, possibly because of the use of less relevant antigens. 4,11 In the present study, the whole-cell antigen extract from the H. pylori strain NCTC 11637 gave reasonable accuracy in an Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' sera were screened for IgG antibodies against H. pylori using a standard enzyme-linked immunosorbent assay (ELISA) test (Pyloriset, Orion, Espoo, Finland) according to the manufacturer's instructions [27].…”
Section: Patients Biopsies and Seramentioning
confidence: 99%
“…In recent years, several diagnostic methods for detecting H. pylori infection have been developed and they can be divided into two clinical groups: (i) invasive methods, requiring endoscopy (i.e. histologic evaluation, culture, the rapid‐urease test or PCR performed on gastric biopsy specimens obtained at endoscopy) and (ii) non‐invasive tests, mainly urea breath tests and serologic measurement of anti‐ Helicobacter pylori (anti‐Hp) antibodies (4,5).…”
Section: Introductionmentioning
confidence: 99%